Potential benefits of ICT for youth agro-based entrepreneurs in Malaysia - Ramli, Siti Aisyah; Abu Samah, Bahaman; Hassan, Md. Salleh; Omar, Siti Zobidah; Bolong, Jusang; Mohamed Shaffril, Hayrol Azril (Asian Network for Scientific Information, 2015)
Information Communication Technology (ICT) offers an abundance of benefits to users, particularly in relation to socio-economic aspects. Agro-based entrepreneurs are one group of users that has experienced such benefits. Additionally, young agro-based entrepreneurs are able to access more opportunities due to their superior ICT knowledge and compatibility. The present study aims to identify the potential benefits of ICT usage for youth agro-based entrepreneurs. Through document analyses, it can be concluded that the benefits offered from ICT to youth agro-based entrepreneurs include improving operational efficiency, increasing income, strengthening marketing aspects and creating new opportunities. With all of these potential benefits in place, it is hoped that consistent involvement from youths in the agriculture industries can be ensured.